Effect of Chitosan Oligosaccharides on the Growth of Bifidobacterium Species - Nurhayati, Yusof; Che Abdullah, Abu Bakar; John Tang, Yew Huat (2016)
The aim of this study was to determine the effect of chitosan and chitosan oligosaccharides (COS), prepared by enzymatic hydrolysis with cellulase from Trichoderma reesei, Celluclast® on the growth of Bifidobacterium sp. The growth of the two bacteria strains were determined every 12 h for 48 h under anaerobic incubation at 37 °C in four MRS media containing lactose, COS, chitosan and inulin. The bacteria cell growth in substrate-added medium increased significantly after 48 h of incubation, except for the chitosan medium. COS was found to have a similar growth effect on B. bifidum ATCC 11863 and B. breve ATCC 15700 when compared with inulin and lactose. The pH of medium containing COS, inulin and lactose fermented with B. bifidum ATCC 11863 and B. breve ATCC 15700 decreased rapidly after 12 h. B. bifidum ATCC 11863 showed the highest specific growth rate at 12 h. The results revealed that COS support the growth of probiotic bacteria, thus indicating that COS has the potential as new prebiotic source in the functional food industry.